Exploring Students’ Conceptual Understanding of Statistics Towards The Problem Based Learning (PBL) Model in Grade XI - Priska Antonia Naikofi; Meiva Marthaulina Lestari Siahaan; Dominifridus Bone (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2026)
This study aims to explore Grade XI students’ concept understanding of statistics at SMA Negeri 1 Insana through the implementation of the Problem Based Learning (PBL) model. A qualitative case study approach was employed through classroom observation, concept-understanding tests, LKS analysis, and student interviews. The findings showed that PBL encouraged active engagement in understanding the concepts of mean, median, and mode through real-world problem exploration. Students’ conceptual understanding improved based on test results: 1 student achieved very good, 26 good, and 3 fair. The average conceptual understanding score was 78.31 (good category). Teacher activity reached 70% (fairly good), while student activity reached 68% (fair). These findings indicate that PBL supports students in independently and contextually constructing their conceptual understanding. In conclusion, the PBLmodel effectively enhances students’ conceptual understanding of statistics, as shown by the dominance of students in the good category. The implications of this study indicate that PBL can be applied as an alternative instructional approach to improve conceptual understanding and learning engagement in statistics. Teachers are encouraged to strengthen the reflection and feedback stages to further support students’ mastery of concepts.